2021
DOI: 10.1111/desc.13073
|View full text |Cite
|
Sign up to set email alerts
|

When event knowledge overrides word order in sentence comprehension: Learning a first language after childhood

Abstract: Limited language experience in childhood is common among deaf individuals, which prior research has shown to lead to low levels of language processing. Although basic structures such as word order have been found to be resilient to conditions of sparse language input in early life, whether they are robust to conditions of extreme language delay is unknown. The sentence comprehension strategies of post‐childhood, first‐language (L1) learners of American Sign Language (ASL) with at least 9 years of language expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…For example, Newport (1990) reports no differences among three groups of ASL signers (native, early, and late) in their acquisition of basic word order. Similarly, for adolescents acquiring a sign language as a first language, Ramirez et al (2013) found the use of relatively short and non-complex utterances, and the acquisition of declaratives earlier than more syntactically complex utterances such as Wh-questions, although they might still differ in the strategies (e.g., event knowledge rather than basic word order) that they use to comprehend sentences (Cheng and Mayberry, 2021). Similarly, Cheng and Mayberry (2019) provide further evidence for the resilience of simple syntactic structures to the effects of delayed language exposure.…”
Section: Types Of Classifier Handshapes In Classifier Constructionsmentioning
confidence: 99%
“…For example, Newport (1990) reports no differences among three groups of ASL signers (native, early, and late) in their acquisition of basic word order. Similarly, for adolescents acquiring a sign language as a first language, Ramirez et al (2013) found the use of relatively short and non-complex utterances, and the acquisition of declaratives earlier than more syntactically complex utterances such as Wh-questions, although they might still differ in the strategies (e.g., event knowledge rather than basic word order) that they use to comprehend sentences (Cheng and Mayberry, 2021). Similarly, Cheng and Mayberry (2019) provide further evidence for the resilience of simple syntactic structures to the effects of delayed language exposure.…”
Section: Types Of Classifier Handshapes In Classifier Constructionsmentioning
confidence: 99%
“…Cormier et al (2012) used a British Sign Language (BSL) version of Boudreault and Mayberry's task and report that accuracy in the grammatical judgement task decreases with age of exposure for deaf signers exposed to BSL between 2 and 8 years of age. In more recent work, Cheng and Mayberry (2020) found that late signers may have significant problems in comprehending even simple sentences with the canonical SVO order if the sentence describes an implausible situation (for example, the ASL counterpart of the sentence 'a duck carries a clown' is incorrectly associated to a picture representing a clown carrying a duck). This suggest that grammatical knowledge is weak enough in these late signers to be overridden by world knowledge.…”
Section: Age Of Exposure Effectsmentioning
confidence: 99%
“…The school's admission policy likely caused many deaf children, particularly those without access to visual language at home, to experience language deprivation in childhood, an experience which can have negative consequences for language acquisition. The age at which an individual acquires a sign language has been shown to affect language processing (Morford, 2003 ), second language acquisition (Mayberry et al, 2002 ), as well as the acquisition of verbs and basic word order in ASL (Newport, 1988 ; Cheng and Mayberry, 2020 ). When late learners transmit language to a subsequent generation, the language system itself may have varying levels of complexity and consistency (Senghas and Coppola, 2001 ; Singleton and Newport, 2004 ).…”
Section: Relationships Among Spoken Languages and Among Signed Languagesmentioning
confidence: 99%